Physical–mechanical behavior of binary cements blended with thermally activated coal mining waste. (30th November 2015) - Vegas, I.; Cano, M.; Arribas, I.; Frías, M.; Rodríguez, O.
Highlights: The influence of different percentages of ACMW on the blended cement behavior was evaluated. The incorporation of ACMW modified the technical behavior of blended cements. The new cements complied to the standard requirements. These ACMW can be used as active addition to elaborate future eco-efficient cements. Abstract: This research work deals with the technical viability of manufacturing new eco-efficient cement blended with thermally activated coal mining waste (ACMW). The physical–mechanical results obtained in the present work showed that the addition of ACMW (up to 20% of replacement) modified the physical and mechanical properties of the blended cement matrices. The blended cements required a great water demand, slightly accelerated settings times and revealed gain in compressive strengths at early curing times. In general terms, blended cements containing up to 20% ACMW meet the chemical, physical and mechanical requirements set out by the EN 197-1 European standard.